Estimation of Glomerular Filtration Rate to Adjust Vancomycin Dosage in Critically Ill Patients: Superiority of the Chronic Kidney Disease Epidemiology Collaboration Equation?. Issue 2 (March 2014) - Conil, J. M.; Georges, B.; Breden, A.; Ruiz, S.; Cougot, P.; Fourcade, O.; Saivin, S.
The purpose of this study was to determine the best estimate of glomerular filtration rate (GFR) to adjust vancomycin (VAN) dosage in critically ill patients. Seventy-eight adult intensive care unit patients received a 15 mg/kg loading dose of VAN plus a 30 mg/kg/day continuous infusion. Steady-state concentration was measured 48 hours later and the dose was adjusted to obtain a target concentration ranging from 20 to 25 mg/1. GFR was estimated by measured creatinine clearance (CLCR ), Cockcroft, Modification of Diet in Renal Disease and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations. The required dose providing the target concentration was 36±17 mg/kg/day. The first dosage had to be increased in 51% of all patients and in 84% of trauma patients (highest GFR), but had to be decreased in 17% of patients. The closest relationship between clearances of vancomycin was observed with CKD-EPI to GFR. The correlation between clearances of vancomycin and measured CLCR was significant but was rather poor with Cockcroft and Modification of Diet in Renal Disease equation. On the Bland and Altman plots, measured CLCR provided a lower bias but a larger confidence interval and a weaker precision than CKD-EPI. For VAN dose adjustments in intensive care unit patients, Cockcroft formula and Modification of Diet in Renal Disease should be used with caution. In clinical practice, the physician does not have at their disposal the patient's measured CLCR when prescribing. The CKD-EPI appears to be the best predictor of clearances of vancomycin for calculation of a therapeutic VAN regimen.